APPLICATION OF INTERFERON-α FOR RESPIRATORY INFECTION IN CHILDREN WITH CHRONIC GLOMERULONEPHRITIS - Z.M. Enikeeva; A.Sh. Khasanova; G.F. Minibaeva; L.R. Kalmet'eva; S.R. Nigmatullina; S.N. Targonsky; S.V. Usova (Педиатрическая фармакология)
The article considers results of usage of interferon α against respiratory infection among 30 children with chronic glomerulonephritis. The positive effect of oral introduction of interferon α for patients, (unlike children with glomerulonephritis and respiratory infection who didn't receive such medication) developed as the absence of exacerbation: no negative dynamics were found in the urine, blood testes and immunogram.Key words: glomerulonephritis, respiratory infection, anti-virus therapy, interferon α, children.